A Prospective Life Cycle Assessment of Electrochemical CO2 Reduction to Selective Formic Acid and Ethylene. Issue 19 (22nd September 2022) - Ai, Ling; Ng, Sue‐Faye; Ong, Wee‐Jun
Abstract: Invited for this month′s cover is the group of Prof. Dr. Wee‐Jun Ong at Xiamen University Malaysia. The image shows a model of Xiamen University and is in celebration of the 5 th and 100 th anniversary of Xiamen University Malaysia and Xiamen University, respectively. The cover showcases the institutes as a pillar of renewable nanotechnology research and a key player in the ever‐growing search for sustainable energy. The Research Article itself is available at 10.1002/cssc.202200857 . Abstract : "…achieving circular economy and carbon neutrality in the long run." This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202200857 . View the Front Cover here: 10.1002/cssc.202201701 .